2023
DOI: 10.1021/acs.accounts.3c00184
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structures and Photoredox Chemistry of Tungsten(0) Arylisocyanides

Abstract: complexes are one-photon visible and two-photon NIR photocatalysts for challenging reductive transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
(143 reference statements)
1
1
0
Order By: Relevance
“…According to the abovementioned early study of [Cr­(CNPh) 6 ], additional excited-state distortion of the Cr–CN–Ph bond angles can take place upon MLCT excitation, which can then promote the photodissociation of arylisocyanide units. During the revision process of this paper, a study on isostructural Mo 0 and W 0 complexes with the same L tri ligand as used herein appeared, following our previous works on Mo 0 complexes with chelating isocyanides, , and work on W 0 isocyanides by the Gray/Winkler team. [Mo­(L tri ) 2 ] and [W­(L tri ) 2 ] were not reported to undergo photoinduced ligand dissociation, in line with the general trend that second- and third-row transition metal complexes are less substitution-labile than those incorporating first-row transition metals.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…According to the abovementioned early study of [Cr­(CNPh) 6 ], additional excited-state distortion of the Cr–CN–Ph bond angles can take place upon MLCT excitation, which can then promote the photodissociation of arylisocyanide units. During the revision process of this paper, a study on isostructural Mo 0 and W 0 complexes with the same L tri ligand as used herein appeared, following our previous works on Mo 0 complexes with chelating isocyanides, , and work on W 0 isocyanides by the Gray/Winkler team. [Mo­(L tri ) 2 ] and [W­(L tri ) 2 ] were not reported to undergo photoinduced ligand dissociation, in line with the general trend that second- and third-row transition metal complexes are less substitution-labile than those incorporating first-row transition metals.…”
Section: Discussionsupporting
confidence: 67%
“…Early work performed several decades ago demonstrated that (monodentate) arylisocyanide ligands stabilize chromium in its zerovalent oxidation state and can lead to electronic structures resembling those of well-known isoelectronic Ru II polypyridines. , Closely related W 0 arylisocyanide complexes were found to be strongly luminescent and photoredox active, and this encouraged us to develop chelating arylisocyanide ligands, which led to Mo 0 , Mn I , and Cr 0 complexes featuring 3 MLCT luminescence similar to Ru II polypyridines. Until now, our main focus has been on bidentate ligands, and while we have reported examples of meridionally coordinating tridentate arylisocyanides, , a facially coordinating tridentate arylisocyanide ligand has not been considered by us yet …”
Section: Resultsmentioning
confidence: 99%